Particle size characterization as a support for sediment contamination analysis. Issue 4 (12th June 2017) - Fernandes, Felippe; Poleto, Cristiano
Abstract : Purpose: The purpose of this paper is to analyse the results of particle size profiles carried out in the dam Mãe d'água, located in the metropolitan region of Porto Alegre, Rio Grande do Sul, becoming a tool of support for geochemistry evaluation works of sediments in this basin. Design/methodology/approach: The methodology comprised the particle size analysis of eight cores sampled using the extraction profile technique "Sampling Cores." A total of 56 sub-samples were obtained at different depths, varying between 0 and 52 cm. The particle size analysis of the sub-samples was carried out with the protocol relating to Brazilian analysis standards NBR 7, 181; for determination of the particle size distribution of thick sediments, the sieve method was used, and for fine sediments, the pipette method was used. Findings: The results show that for the different depths, the sediment profiles show similarity in their sedimentary deposition layers. Cores T1, T6, T7 and T8 showed a classification with predominance of mud. Cores T2 and T5 showed variations throughout their sedimentary profile, varying of mud predominance to sand with gravel, and on cores T3 and T4, the predominant characteristic is sand with mud and sand with gravel, respectively. Originality/value: It can be seen in this paper that energy of sedimentological flow reaches it in a different way, creating these three sectors (first, sand with gravel; second, sand with mud and third, mud) with different characteristics – morphodynamic and sedimentological. These characteristics are important for the study of the heavy metals on the soil and therefore for reducing the risk of contamination of water courses.